Preparing myportfolio for section human resource and administration of MAMPU Sarawak / Chulik Angki - Angki, Chulik (University Technology MARA Sarawak, 2018)
According to MAMPU Official Website, MAMPU was established based on a study. "Development Administration in Malaysia" in year 1965 conducted by Prof. John D. Montgomery and Milton J. Esman. The report acknowledged the need to upgrade professionalism in the Public Service through educational and training programmes. Based on recommendations of the report, the Development Administrative Unit (DAU) was established in 1966 to spearhead administrative reforms in the Government. DAU was later expanded and renamed Implementation Coordination Development Administrative Unit (ICDAU) tasked with coordinating the planning and development of human resources. In line with the rapid and dynamic growth of the Public Service, ICDAU was later restructured in 1977. In 1986, the role of human resource planning was reassigned to other agencies so that the agency can focus its efforts on Public Sector administrative modernisation and management consultation. Since then, ICDAU was known as the Malaysian Administrative Modernisation and Management Planning Unit (MAMPU).